Investment in innovation: Corporate governance and employment ; is prosperity sustainable in the United States? - William Lazonick; Mary O'Sullivan (Levy Economics Institute of Bard College, 1997)
Since the 1970s corporate America has become obsessed with shedding employees to cut costs and with distributing revenue to stockholders. However, the way for it to regain its competitive edge and thus to restore the promise of secure and remunerative employment for its workers is to reform its system of governance. It must reject organizational segmentation and extraction of short-term returns and instead emphasize organizational integration and long-term value creation through financial commitment to investment in the collective and cumulative learning that is the foundation of industrial innovation.
Keywords: 330